2020
DOI: 10.1016/j.isci.2020.101538
|View full text |Cite
|
Sign up to set email alerts
|

The Chromosome Level Genome and Genome-wide Association Study for the Agronomic Traits of Panax Notoginseng

Abstract: Summary The Chinese ginseng Panax notoginseng is a domesticated herb with significant medicinal and economic value. Here we report a chromosome-level P. notoginseng genome assembly with a high (∼79%) repetitive sequence content. The juxtaposition with the widely distributed, closely related Korean ginseng ( Panax ginseng ) genome revealed contraction of plant defense genes (in particular R -genes) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 77 publications
0
31
0
Order By: Relevance
“…Four versions of P. notoginseng genome assembly have been reported (Chen et al, 2017; Fan et al, 2020; Jiang et al, 2020; Zhang et al, 2017). The first two assemblies are highly fragmented, which limits genomic studies of P. notoginseng .…”
Section: Figurementioning
confidence: 99%
“…Four versions of P. notoginseng genome assembly have been reported (Chen et al, 2017; Fan et al, 2020; Jiang et al, 2020; Zhang et al, 2017). The first two assemblies are highly fragmented, which limits genomic studies of P. notoginseng .…”
Section: Figurementioning
confidence: 99%
“…In the same year, Chen et al reported a 2.39 Gb whole genome sequence with a scaffold N50 of 96 kb, annotating 36,790 genes (Chen et al 2017 ). In 2020, Fan et al completed a 2.25 Gb assembly consisting of 16,469 scaffolds with a contig N50 220.89 kb and annotated 39,452 genes (Fan et al 2020 ). Jiang et al reported a significantly improved chromosome-level assembly of P. notoginseng .…”
Section: Status Of Genomic Research In the Genus Panaxmentioning
confidence: 99%
“…Ginsenosides and notoginsenosides are steroid-like compounds with diverse pharmacological properties, such as protecting cardiovascular system, immunoregulation, anti-atherosclerotic activity, anti-tumor activity, antioxidant activity, and hemostatic activity (Wang et al, 2016). The annual output values of P. notoginseng has exceeded 10 billion dollars (Fan et al, 2020). Like many valuable medicinal plants, however, P. notoginseng is facing contradictions between increasing market requirements and limited resource caused by cultivation difficulty (Canter et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the arable area of P. notoginseng is restricted to the mountain areas in southwestern China due to its specific ecological requirements (Guo et al, 2010). Besides, the cultivation of P. notoginseng suffers from several replanting diseases which decrease the production quality and yields and further restrict the development of P. notoginseng industry (Fan et al, 2020). A systematical understanding of the ecology of rhizosphere microbiota will provide insights into the alleviation of the cultivating dilemma of medicinal plants (Soberon and Peterson, 2005).…”
Section: Introductionmentioning
confidence: 99%